ACTIVITY OF 96% ETHANOL EXTRACT OF CHRYSOPHYLLUM CAINITO L. IN INCREASING VERTEBRAE TRABECULAR OSTEOBLAST CELL NUMBER IN MALE MICE - Ma’arif, Burhan; Aditama, Agnis Pondinekaria (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study was conducted to analyze the anti-osteoporosis effect of 96% ethanol extract from Chrysophyllum cainito L. leaves, which suspected to contain phytoestrogens, in increasing the osteoblast cell number in trabecular vertebra bone of dexamethasone-induced male mice. Materials and Methods: The 96% ethanol extract of C. cainito leaves was given to male mice with dose of 2, 4, 8, and 16 mg/20 g BB mice/day after being induced orally with dexamethasone dose of 0.0029 mg/20 g BB mice/day. The positive control used was 0.026 ml/20 g BB mice/day alendronate. After 4 weeks, the increasing of osteoblast cell number in trabecular vertebrae bone of male mice was observed using an optical microscope with 100Ã— zoom in after histomorphometry and hematoxylin-eosin staining methods. Results: The result showed the significant increasing of osteoblast number in trabecular vertebrae bone of male mice in all groups after being given treatment using 96% ethanol extract of C. cainito, with an effective dose (ED50) value of 9.5 mg/20 g BB mice/day. This increase is suspected due to the phytoestrogens content, which can also act as phytotestosterone in 96% ethanol extract of C. cainito. Conclusion: This study concluded that 96% ethanol extract of C. cainito has an activity in increasing osteoblast cell number in trabecular vertebra bone of dexamethasone-induced male mice, with an ED50 value of 9.5 mg/20 g BB mice/day.